Community archives' role in safeguarding Intangible Cultural Heritage - Irfaniah, Hikmah (Jurnal Kajian Informasi dan Perpustakaan, 2023)
Safeguarding intangible cultural heritage is an effort requiring the involvement of the cultural community. This study aimed to describe the role of community archives in safeguarding Silat Sutera Baja as an Intangible Cultural Heritage of DKI Jakarta Province. This study was qualitative research with a case study method. The research data were collected by conducting interviews and documentation studies from May 2023 to July 2023. The informants involved in this study were three people selected using a purposive sampling method. Informants were people involved in the process of the stipulation of Silat Sutera Baja as an Intangible Cultural Heritage of Indonesia. They were members of the Silat Sutra Baja community and employees of the local cultural service. Research data analysis was carried out through data reduction by making interview transcripts and coding to answer research questions. The coding findings were then evaluated, interpreted, and confirmed using additional data sources to derive conclusions. Research results showed that community archives, referred to as archival activities, had a role in following the archive life cycle; they were creators, distributors, users, and maintainers. Whereas community archives as collected material played their role as memory and identity. These archives showed Silat Sutera Baja’s identity and their collective memory as part of the Silat Putera Betawi. Based on the results, people need to dissolve archives by converting print archives to digital format and using cloud-based repositories such as Google Drive so that they are not lost.